Multiplex PCR in noninvasive prenatal diagnosis for FGFR3‐related disorders. (15th April 2018) - Terasawa, Sumire; Kato, Asuka; Nishizawa, Haruki; Kato, Takema; Yoshizawa, Hikari; Noda, Yoshiteru; Miyazaki, Jun; Ito, Mayuko; Sekiya, Takao; Fujii, Takuma; Kurahashi, Hiroki
ABSTRACT: Thanatophoric dysplasia and achondroplasia are allelic disorders caused by a constitutively active mutation in the FGFR3 gene. Because thanatophoric dysplasia is a lethal disorder and achondroplasia is non‐lethal, they need to be distinguished after ultrasound identification of fetal growth retardation with short limbs. Accordingly, we have developed a noninvasive prenatal test using cell‐free fetal DNA in the maternal circulation to distinguish thanatophoric dysplasia and achondroplasia. A multiplex PCR system encompassing five mutation hotspots in the FGFR3 gene allowed us to efficiently identify the responsible mutation in cell‐free DNA in all examined pregnancies with a suspected thanatophoric dysplasia or achondroplasia fetus. This system will be helpful in the differential diagnosis of thanatophoric dysplasia and achondroplasia in early gestation and in couples concerned about the recurrence of thanatophoric dysplasia due to germinal mosaicism.